1)=8а²(в²-9с²)=8а²(в-3с)(в+3с).
2)=2(х²-12ху+36у²)=2(х-6у)².
3)=-2а(4а4-4а²+1)= -2а(2а²-1)².
4)=5(а³-8в6)=5(а³-(2в²)³)=5(а-2в²)(а²+2ав²+4в4)
5)=(а³+а²)-(ав-а²в)=а²(а+1)-ав(1+а)=(а+1)(а²-ав)=а(а+1)(а-в)
6)=с4(а-1)-с²(а-1)=(а-1)(с4-с²)=с²(а-1)(с²-1)=с²(а-1)(с-1)(с+1).
1)=(х-у)²-7²=(х-у-7)(х-у+7)
2)=а²-(3в-с)²=(а+3в-с)(а-3в+с)
3)=(в³)²-(2в²-3)²=(в³+2в²-3)(в³-2в²+3).
4)=(m³+3³n³)+(m+3n)²=(m+3n)(m²-3mn+9n²)+(m+3n)²=(m+3n)(m²-3mn+9n²+m+3n).
5)=x²-y²+2x+4y-3=(x²+2x+1)-(y²-4y+4)=(x+1)²-(y-2)²=(x+y-1)(x-y+3).
2)14mn^2-7n=7n(2mn-1)
3)-20c^2+80 bc=20c(4b-c)
4)a^4+a^3=a^3(a+1)
5)5x^5-4x^3=x^3(5x^2-4)
6)ax^2+3ax=ax(x+3)
7)3c^6+7c^7-8c^8=c^6(3+7c-8c^2))
8)5x^2-10x^3-15x^4=5x^2(1-2x-3х^2))
9)3a^3b-6a^2b^2=3a^2b(a-2b)
10)6c^2x^3-4c^3x^2+2c^2x^2=2c^2x^2(3x-2c+1))
(4х+3)(х+4)-(3х+5)(2х+4)+х(2х+3)=4x²+3x+16x+12-6x²-10x-12x-20+2x²+3x=
+3x+16x-22x+12-20+3x=(16x+6x-22x)=12-20=-8
выражение равно -8,не зависит от переменной х